Protective and Detoxifying Enzyme Activity and ABCG Subfamily Gene Expression in Sogatella furcifera Under Insecticide Stress - Zhou, Cao; Yang, Hong; Wang, Zhao; Long, Gui-Yun; Jin, Dao-Chao (Frontiers in Physiology, 2019)
Sogatella furcifera, an important migratory pest of rice, considerably affects rice production. To clarify the mechanism by which S. furcifera responds to insecticide stress, we measured the activity of its protective (superoxide dismutase, SOD; peroxidase, POD; catalase, CAT) and detoxifying (carboxylesterase, CarE; glutathione S-transferase, GST; mixed function oxidase, MFO) enzymes and the expression levels of its ATP-binding cassette subfamily G (ABCG) transporter genes at sublethal concentrations (LC10 and LC25) of thiamethoxam, buprofezin, and abamectin. Based on transcriptome data and the ABCG genes of Laodelphax striatellus, we obtained 14 full-length ABCG sequences for S. furcifera. RT-qPCR results showed that 13, 12, and 9 sfABCG genes were upregulated in the presence of thiamethoxam, buprofezin, and abamectin, respectively, at LC10. Moreover, 13 and 7 sfABCG genes were upregulated following treatment with thiamethoxam and abamectin, respectively, at LC25. The enzyme activity assays showed that although thiamethoxam, buprofezin, and abamectin were able to induce GST, CarE, CAT, POD, and SOD activity, they did so at different concentrations and at different exposure times. The activity of MFO was inhibited overall with prolonged exposure to the three insecticides, with the inhibitory effect being the most significant at 72 h. These results indicate that the response of S. furcifera to different types or concentrations of insecticides is different. Taken together, our results lay a foundation for a deeper understanding of the mechanisms of S. furcifera adaptation to different types of insecticides, which would be of great significance for the development of effective pest management strategies.